TINGKAT KETAHANAN PANGAN RUMAH TANGGA DI DESA TERTINGGAL - Imron Rosyadi; Didit Purnomo (Muhammadiyah University Press, 2012)
The purpose of this study was to determine the level of production, availability of food for the community and analyze the level of accessibility of food for households in villages in the district behind Weru Sukoharjo. The method of analysis used in qualitative research is descriptive analytic in order to approach the situation, structure, behavior and performance (SSPP). Use of this approach is based on the consideration of allegations that sensitive (vulnerable) of food a lot happening in the villages left behind. The results of this study indicate that the performance of food production especially rice or rice has increased significantly from year to year, but increased production has not been able to offset the growth in consumption of rice that grows higher than the growth in rice production. This shows that in terms of food availability, food security in the area of research is still very low.